2017
DOI: 10.1039/c7ra05732f
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic carbon nitride nanosheets obtained by liquid stripping as efficient photocatalysts under visible light

Abstract: Well-scattered g-C3N4 nanosheets obtained using a liquid stripping possess much higher photocatalytic performance than bulk g-C3N4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 41 publications
3
25
0
Order By: Relevance
“…The intensity of ZnO stretching vibration observed at 570 cm −1 are decreased in the order of Zn-U1 > Zn-U2 > Zn-U3 nanocomposite and almost disappear in the case of Zn-U3. The small peaks appearing at 275 cm −1 , 510 cm −1 , 645 cm −1 , 860 cm −1 , and 1157 cm −1 are characteristic of the g-C 3 N 4 and agreed well with the reported literature [38,[41][42][43]. Thus, the observed Raman scattering results confirmed that the synthesized sample is composed of g-C 3 N 4 and ZnO and match well with the XRD results.…”
Section: Raman Spectroscopysupporting
confidence: 91%
“…The intensity of ZnO stretching vibration observed at 570 cm −1 are decreased in the order of Zn-U1 > Zn-U2 > Zn-U3 nanocomposite and almost disappear in the case of Zn-U3. The small peaks appearing at 275 cm −1 , 510 cm −1 , 645 cm −1 , 860 cm −1 , and 1157 cm −1 are characteristic of the g-C 3 N 4 and agreed well with the reported literature [38,[41][42][43]. Thus, the observed Raman scattering results confirmed that the synthesized sample is composed of g-C 3 N 4 and ZnO and match well with the XRD results.…”
Section: Raman Spectroscopysupporting
confidence: 91%
“…When the Pd loading process was finished, the ultra-small Pd NPs were uniformly dispersed on the surface of ultrathin crystalline g-C 3 N 4 (Figure e). From the XRD pattern, it can be found that the intensity of the peak for ultrathin crystalline g-C 3 N 4 sharply decreased in comparison with that of bulk g-C 3 N 4 , owing to the successful exfoliation of bulk g-C 3 N 4 . The Raman spectrum of ultrathin crystalline g-C 3 N 4 shifted to lower wavelength compared to the bulk sample (Figure b), further indicating the formation of an ultrathin nanosheet . The diffraction peaks of metallic Pd were at 39.5° (111), and 45.6° (002). , For the Pd/g-C 3 N 4 prepared in this work, the characteristic peaks of metal Pd were broadened (Figure a), which should be ascribed to the small size.…”
Section: Results and Discussionmentioning
confidence: 96%
“…28−30 The Raman spectrum of ultrathin crystalline g-C 3 N 4 shifted to lower wavelength compared to the bulk sample (Figure 1b), further indicating the formation of an ultrathin nanosheet. 31 The diffraction peaks of metallic Pd were at 39.5°(111), and 45.6°( 002). 32,33 For the Pd/g-C 3 N 4 prepared in this work, the characteristic peaks of metal Pd were broadened (Figure 1a), which should be ascribed to the small size.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As shown in Figure 1b, the broad band from 3000 to 3500 cm −1 was attributed to primary (−NH) and secondary amines (−NH 2 ) from the hydrogenation of sp 2 ‐N. [ 33,34 ] There were five characteristic peaks at 1229, 1311, 1456, 1537 and 1627 cm −1 , all of which were attributed to the skeletal vibrations of the heptazine heterocyclic ring (C 6 N 7 ) units. The stretching vibration of the s ‐triazine ring (C 3 N 3 ) unit was located at 810 cm −1 .…”
Section: Resultsmentioning
confidence: 99%